Roots of the Malformations of Cortical Development in the Cell Biology of Neural Progenitor Cells - Ossola, Chiara; Kalebic, Nereo (Frontiers in Neuroscience, 2022)
The cerebral cortex is a structure that underlies various brain functions, including cognition and language. Mammalian cerebral cortex starts developing during the embryonic period with the neural progenitor cells generating neurons. Newborn neurons migrate along progenitors’ radial processes from the site of their origin in the germinal zones to the cortical plate, where they mature and integrate in the forming circuitry. Cell biological features of neural progenitors, such as the location and timing of their mitoses, together with their characteristic morphologies, can directly or indirectly regulate the abundance and the identity of their neuronal progeny. Alterations in the complex and delicate process of cerebral cortex development can lead to malformations of cortical development (MCDs). They include various structural abnormalities that affect the size, thickness and/or folding pattern of the developing cortex. Their clinical manifestations can entail a neurodevelopmental disorder, such as epilepsy, developmental delay, intellectual disability, or autism spectrum disorder. The recent advancements of molecular and neuroimaging techniques, along with the development of appropriate in vitro and in vivo model systems, have enabled the assessment of the genetic and environmental causes of MCDs. Here we broadly review the cell biological characteristics of neural progenitor cells and focus on those features whose perturbations have been linked to MCDs.